Education Intervention and Leadership / Intervention éducative et leadership - Park, Hyeyung; Fahlman, Rob (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2026)
The aquaculture industry plays a crucial role in food security, employment, and economic development. However, the planned phase-out of open net-pen salmon farming brings significant challenges, including environmental concerns, economic uncertainty, and the need for regulatory adaptations. Indigenous communities, which are heavily reliant on aquaculture, face financial and technical constraints. Moreover, the absence of a dedicated postsecondary program in aquaculture management impairs sustainable business innovation. This study proposes a Bachelor of Management in Aquaculture (BMA) as an education intervention to tackle social and economic challenges. The BMA program combines business management, aquaculture operations, and Indigenous knowledge, equipping graduates with the strategic skills needed for sustainable aquaculture. Delivered through blended learning, the program promotes flexibility, accessibility, and collaboration within the industry. Guided by transformational leadership within a quintuple helix innovation model, this initiative emphasizes collective interaction among government, academia, Indigenous groups, industry, and the environment. By bridging knowledge gaps and promoting innovation, the BMA program represents a critical step toward strengthening the aquaculture sector, ensuring economic resilience, and fostering sustainable environmental stewardship. The study emphasizes the importance of education intervention and leadership to address social and economic problems.